2016
DOI: 10.5941/myco.2016.44.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase Inhibitors from the Fruiting Body of Phellinus igniarius

Abstract: During our ongoing investigation of neuraminidase inhibitors from medicinal fungi, we found that the fruiting bodies of Phellinus igniarius exhibited significant inhibitory activity against neuraminidase from recombinant H3N2 influenza viruses. Two active compounds were isolated from the methanolic extract of P. igniarius through solvent partitioning and Sephadex LH-20 column chromatography. The active compounds were identified as phelligridins E and G on proton nuclear magnetic resonance (1H NMR) and electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The components in Phellinus igniarius also showed good antiviral activity. Two compounds, the phelligridins E and G were isolated from the methanol extract of Phellinus igniarius fruiting bodies, which showed neuraminidase inhibitory activity against recombinant H1N1, H3N2, and H5N1 in a dose-dependent manner [ 19 ]. An in vitro experiment of Phellinus igniarius aqueous extract PIW shows that it has inhibitory activity on 2009 pandemic H1N1, human H3N2, avian H9N2, and oseltamivir-resistant H1N1 viruses, and its mechanism may be related to interfering with the early replication process of the virus [ 20 ].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…The components in Phellinus igniarius also showed good antiviral activity. Two compounds, the phelligridins E and G were isolated from the methanol extract of Phellinus igniarius fruiting bodies, which showed neuraminidase inhibitory activity against recombinant H1N1, H3N2, and H5N1 in a dose-dependent manner [ 19 ]. An in vitro experiment of Phellinus igniarius aqueous extract PIW shows that it has inhibitory activity on 2009 pandemic H1N1, human H3N2, avian H9N2, and oseltamivir-resistant H1N1 viruses, and its mechanism may be related to interfering with the early replication process of the virus [ 20 ].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…The study on neuraminidase inhibitors also demonstrated the efficacy of P. igniarius extracts against the influenza virus. Two active compounds, phelligridin E and G, were isolated from the methanolic extract and were identified as neuraminidase inhibitors of H1N1, H3N2, and H5N1 strains with IC 50 values in the range of 0.7∼8.1 μM [50] …”
Section: Phellinus Igniariusmentioning
confidence: 99%
“…P. igniarius is rich in secondary metabolites with biological activities, such as polysaccharides, polyphenols, flavonoids, and other chemical species [ 4 , 5 ]. Phelligridins are a class of chemical compounds from P. igniarius that possess radical-scavenging activity and a broad range of pharmacological properties, and includes chemicals such as Phelligridin D and Phelligridin G [ 6 , 7 ]. Based on structural analyses, it has been postulated that hispidin is a key intermediate of phelligridins [ 8 ].…”
Section: Introductionmentioning
confidence: 99%